2008
DOI: 10.1261/rna.1202108
|View full text |Cite
|
Sign up to set email alerts
|

The sarcin–ricin loop of 23S rRNA is essential for assembly of the functional core of the 50S ribosomal subunit

Abstract: The sarcin-ricin loop (SRL) of 23S rRNA in the large ribosomal subunit is a factor-binding site that is essential for GTP-catalyzed steps in translation, but its precise functional role is thus far unknown. Here, we replaced the 15-nucleotide SRL with a GAAA tetraloop and affinity purified the mutant 50S subunits for functional and structural analysis in vitro. The SRL deletion caused defects in elongation-factor-dependent steps of translation and, unexpectedly, loss of EF-Tu-independent A-site tRNA binding. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 72 publications
1
55
0
Order By: Relevance
“…Here, it is essential to consider the effect of the sarcin-ricin loop (SRL) of the 23S rRNA, and in particular residue A2662 (see Fig. S2), whose critical role has been pointed out before (14)(15)(16). Significantly, our simulations of the EF-Tu′/ribosome complex found that a proper H84 positioning, without any additional artificial force constraints, required the presence of the SRL loop with its A2662 residue.…”
Section: Figmentioning
confidence: 91%
See 1 more Smart Citation
“…Here, it is essential to consider the effect of the sarcin-ricin loop (SRL) of the 23S rRNA, and in particular residue A2662 (see Fig. S2), whose critical role has been pointed out before (14)(15)(16). Significantly, our simulations of the EF-Tu′/ribosome complex found that a proper H84 positioning, without any additional artificial force constraints, required the presence of the SRL loop with its A2662 residue.…”
Section: Figmentioning
confidence: 91%
“…Breakthrough in the elucidation of the ribosome structure (2-13) and careful biochemical studies (1)(2)(3)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) allow one to begin thinking about the nature of the mechanism of the elongation process. In particular, the elucidation of structure of the EF-Tu/ribosome complex (our study refers to the structure of EF-Tu in the complex as EF-Tu′) (9) opens the way for the exploration of the activation process at the molecular level.…”
mentioning
confidence: 99%
“…Here, it is important to consider the effect of the SRL of the 23S rRNA subunit, and, in particular the role of residue A2662 (see Fig. 33 for relative positions), whose critical role has been already pointed out elsewhere (Hausner et al 1987 ;Lancaster et al 2008 ;Moazed et al 1988). Significantly, our simulations of the EF-Tu'/ribosome complex found that the presence of the SRL loop (with its A2662 residue) was essential for the proper positioning of H84 (without any additional artificial force constraints).…”
Section: Efs and Ribosomal Activationmentioning
confidence: 99%
“…In contrast, mutations to the loop E motif are extremely detrimental to the function of the inhibitor (Townsend et al 2008b). Loop E motifs are known to interact with proteins and to be involved in RNA-RNA interactions (Hausner et al 1987;Moazed et al 1988;Leontis and Westhof 1998;Lancaster et al 2008). Both types of interactions may play a role in the ciRNA's function.…”
Section: Discussionmentioning
confidence: 99%